Enterobacter Sakazakii and Salmonella in powdered infant formula : (FAO/WHO, 2006)
Following the analysis of new and additional information and the development of a more extensive risk assessment on E. sakazakii in powdered infant formula, this volume aims to provide the most up-to-date information on these microorganisms, the risk associated with their presence in powdered infant formula and scientific advice to facilitate the management of that risk.